Resettling, disconnecting or displacing? Attending to local sociality, culture and history in disaster settings. (26th July 2019) - Hsu, Minna; Okada, Tetsuya; Mori, Suguru; Howitt, Richard
Abstract : In many disaster settings, top‐down responses emphasise 'expert‐led' solutions that often involve relocating disaster‐affected communities. While the intention might be to move people from harm's way and facilitate recovery, failure to attend to local pre‐disaster circumstances as well as the interplay between power, resilience and vulnerability within and around affected communities often sees resettlement reconfigure as displacement or disconnection. This oversight may even usher in a new phase of dispossession and disadvantage for marginalised groups (particularly in colonial settings). This paper explores experiences in Australia, Japan and Taiwan to reflect on what issues of local sociality, local culture and local resilience need to be attended to in framing 'better' disaster responses.